Retrospective evaluation of the autoacoustic emission test and auditory brainstem response in risky newborns - Yavanoğlu Atay, Funda; Atay, Gürkan; Nuhoğlu, Çağatay; Ceran, Ömer (Kare Yayıncılık, 2020)
Introduction: The early development of the sense of hearing in the baby affects both language and language development considerably, as well as emotional, social and mental development. Hearing loss, which higher in newborns with risk factors, is 1-2% incidence in 1000 live births. Evoked Otoacoustic Emissions (EOAE) and Auditory Brainstem Response (ABR) methods are used in neonatal hearing screenings. We aimed to evaluate the EOAE and ABR results of the newborns in this study and the comparison of the two tests. Methods: Between January 2011 and July 2011, 104 newborns with a high-risk factor in our hospital were evaluated retrospectively. Results: The risk factors for the congenital anomaly, be in intensive care and neonatal hyperbilirubinemia, were found to be statistically significantly higher in the Hearing Loss group (+) than in the Hearing Loss group (-). In logistic regression analysis, it was determined that neonatal hyperbilirubinemia was a significant risk factor for hearing loss. Discussion and Conclusion: Our findings contributed to the national data and our findings suggest that neonatal hyperbilirubinemia increases the risk of hearing loss.
Keywords: Hhearing Loss; Neonatal Hyperbilirubinemia; Otoacoustic Emissions